Diccionario Biográfico de Escritores Costarricenses (DIBEC). Esbozo de un proyecto. - Sánchez Mora, Alexander (Káñina, 2012)
Biographical dictionaries are a type of textual production that has lacked enough prestige in either literary or lexicographical field.This marginal condition has affected its development in Costa Rica. This article is aimed to both defend the outstanding function of the biographical dictionary as a basic reference book, and introduce the project of the production of Diccionario Biográfico de Escritores Costarricenses (DIBEC) Biographical Dictionary of Costa Rican Writers (DIBEC).